Ru(iii) -based polyoxometalate tetramers as highly efficient heterogeneous catalysts for alcohol oxidation reactions at room temperature. Issue 36 (19th August 2021) - Zou, Yan; Li, Huafeng; Zhao, Xue; Song, Junpeng; Wang, Yaqiong; Ma, Pengtao; Niu, Jingyang; Wang, Jingping
Abstract : Robust tetra-Ru-containing POMs show strong ability in achieving catalysis for the oxidation of 1-(4-chlorophenyl)ethanol to 4′-chloroacetophenone at room temperature. Abstract : A novel ruthenium-containing polyoxometalate-based organic–inorganic hybrid, K4 Na9 H7.4 [(AsW9 O33 )4 (WO2 )4 Ru3.2 (C3 H3 N2 )2 ]·42H2 O (1 ), was successfully synthesized by a one-step hydrothermal method under acidic conditions, which applied a self-assembly strategy between inorganic polyoxometalate based on trivacant [B-α-AsW9 O33 ] 9− AsW9 fragments and an organic ligand, imidazole (C3 H4 N2 ). Compound 1 was further characterized by single-crystal X-ray diffraction, PXRD, IR spectroscopy, UV-Vis spectroscopy, ESI-MS, elemental analysis and TGA. Single-crystal X-ray diffraction data reveal that the polyanion consists of four trivacant Keggin-type polyanion AsW9 building blocks bridged by four WO6 units, leading to a crown-shaped tetrameric structure [(AsW9 O33 )4 (WO2 )4 Ru3.2 (C3 H3 N2 )2 ] 20.4− . The ESI-MS result reveals that the polyanion unit has excellent structural integrity in water. Moreover, the catalysis study of 1 was also further investigated, and the experimental results indicate heterogeneous catalyst 1 presents high efficiency (yield = 98%), excellent selectivity (>99%), and good recyclability for the oxidation of 1-(4-chlorophenyl)ethanol to 4′-chloroacetophenone with commercially available 70% aqueous tert -butyl hydroperoxide TBHP (aq.) as the oxidant at room temperature.